2024
DOI: 10.1007/s11119-024-10122-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training sample size, sampling design and prediction model on soil mapping with proximal sensing data for precision liming

Jonas Schmidinger,
Ingmar Schröter,
Eric Bönecke
et al.

Abstract: Site-specific estimation of lime requirement requires high-resolution maps of soil organic carbon (SOC), clay and pH. These maps can be generated with digital soil mapping models fitted on covariates observed by proximal soil sensors. However, the quality of the derived maps depends on the applied methodology. We assessed the effects of (i) training sample size (5–100); (ii) sampling design (simple random sampling (SRS), conditioned Latin hypercube sampling (cLHS) and k-means sampling (KM)); and (iii) predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Concordance increased quickly, while RMSE decreased quickly, as a function of sample size. This aligns with similar studies that show model performance metrics improve quickly at smaller sample sizes and then gradually level off [12,20]. In general, the sample plans selected with cLHS and FSCS outperformed those created with SRS in terms of both performance metrics at smaller sample sizes.…”
Section: Optimal Sample Size-learning Curvessupporting
confidence: 88%
See 2 more Smart Citations
“…Concordance increased quickly, while RMSE decreased quickly, as a function of sample size. This aligns with similar studies that show model performance metrics improve quickly at smaller sample sizes and then gradually level off [12,20]. In general, the sample plans selected with cLHS and FSCS outperformed those created with SRS in terms of both performance metrics at smaller sample sizes.…”
Section: Optimal Sample Size-learning Curvessupporting
confidence: 88%
“…For example, Bouasria et al [14] showed minimal difference in RF model performance when comparing sample plans developed from cLHS and SRS to predict aboveground biomass, and Loiseau et al [83] noted no substantial difference in quantile RF predictions of sand, silt, and clay between SRS and cLHS sample plans. Schmidinger et al [12] noted higher RMSE and lower CCC with SRS compared to cLHS and FSCS at smaller sample sizes, whereas the differences decreased as sample sizes increased until all three sampling designs showed the same performance. To the contrary, Ma et al [82] showed that the overall accuracy of soil class prediction with RF was better with FSCS than it was with cLHS and SRS.…”
Section: Optimal Sample Size-learning Curvesmentioning
confidence: 98%
See 1 more Smart Citation